Lineage in the vertebrate retina - Cayouette, Michel; Poggi, Lucia; Harris, William A. (Trends in neurosciences, 2006)
Recent results are changing the way we think about cell-fate decision mechanisms in the retina. For a long time it was accepted that lineage was not important in retinal cellular determination but, as we review here, new data show that lineage programmes might be at the heart of this process. These programmes are intrinsic, but they are also plastic and are influenced by extrinsic signals.
Gesehen am 24.05.2017